2011
DOI: 10.3399/bjgp11x561203
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity trends in the population of a specialised homeless primary care service

Abstract: An increasing body of research demonstrates that homelessness is an independent risk factor for morbidity and premature death. This paper compares the frequency of diagnoses between 2003 and 2009 in the computerised records of a specialist practice for homeless people. The changing morbidity trends revealed offer a basis for comparison with other services and suggest benefits from collaborative working, particularly around substance misuse and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…6 However, estimates of substance misuse rates vary according to the population sampled; a Leicester series found that around half of the homeless patients had neither drug nor alcohol dependence. 7 …”
Section: Medical Problems Associated With Homelessnessmentioning
confidence: 99%
“…6 However, estimates of substance misuse rates vary according to the population sampled; a Leicester series found that around half of the homeless patients had neither drug nor alcohol dependence. 7 …”
Section: Medical Problems Associated With Homelessnessmentioning
confidence: 99%
“…The sample was diversified by age, sex, type of exercise and structure of the exercise. Most of them13 were either employed or had mixed practice. None of them declared receiving any patient with a high or very high social level (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…9 These people suffer from higher morbidity9–11 and earlier mortality compared with people with stable housing. The average age of death is between 40 and 50 years12 13 and the standardised mortality ratios in high-income countries is typically reported from 2 to 5 times the age-standardised general population 9…”
Section: Introductionmentioning
confidence: 99%
“…Homeless adults have a high level of morbidity (Hewett, Hiley, & Gray, 2011) and mortality (Baggett et al, 2013), oftentimes due to unmet physical and mental health needs. Across the nation, physical and mental healthcare needs have been documented among homeless adults (Brown, Kiely, Bharel, & Mitchell, 2012; Garibaldi, Conde-Martel, & O'Toole, 2005; Kertesz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%